Assistingthe government in the implementation Non-formal education: a case study of the Indonesian kasih bundo institute for the care and development of the disable children - Bayu, Eka Pasca Surya; Meilisa, Mira (COUNS-EDU: The International Journal of Counseling and Education, 2017)
Poverty is still a serious issue worlwide including in Indonesia. One important way to address it is by providing education by the government. However, the government alone cannot address the problem satisfactorily, and, therefore, it needs non-governmental organisations (NGOs) to assist. One of these type of NGOs is Yayasan Penyantun dan Pembina Anak Cacat (YPPAC) Kasih Bundo. This NGO assists the government by providing a non-formal education by establishing Pusat Kegiatan Belajar Masyarakat (PKBM) Kasih Bundo (The Kasih Bundo Study Centre for the Community). This article reports a study on this NGO, focusing on what it has done and what it has successfully achieved by looking at the social and economic background of their families. The result suggests that the NGO has successfully assisted the government in a significant manner.